(3EjSGZhLj (B- (3aj GdWHs - (3JQLeI LGdjfjhSs
(3ChdgG (B:s
(3bGd LGdjfhS(B: (3Edi ce LRA jfbSe GdWH bGd(B: (3Edi LRFjf, bGd heG geG bGd(B: (3GdYde hGdYde Edi ce LRA jfbSe GdYde bGd(B: (3Edi KdGKI CLRGA bGd(B: (3heG gj bGd(B: (3GdYde HeYQaI GdCehQ GdWHjYjI s
(3BNQgG (B:s
(3CeG OdGdJg Ydi Cf GdYdI aj LejY GdHOf aeKd eG jOd aj GdMei haj GdbVjH ef GdQLd haj GdaQL ef GdeQCI s
(3eUhQI Yf GdeJMa GdHQjWGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
GALS - (3GdLRA (B3 - (3U (B139 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B1103) s
Keywords: (3GdWHs